Staphylococcus aureus, nosilec gena za Panton-Valentine leukocidin, in letalna nekrotizirajoča pljučnica pri mladem imunokompetentnem bolniku - Piltaver-Vajdec, Irena (Zdravniški vestnik, 2006)
Background Staphylococcus aureus (S. aureus) is a major cause of hospital-acquired infections. It secretes many exotoxins, in less then 5% alsoPanton-Valentine leukocidin (PVL). S. aureus carrying PVL genes is mainly associated with necrotic lesions of skin and mucosa and can cause severe necrotising community-acquired pneumonia. Methods We describe a case of a 30 year-old patient with a history of furunculosis who was admitted to our hospital with atypical lower abdominal pain. A clinical picture of acute abdomen developed and he was operated with no intraabdominal pathology found. A periprocedural respiratory insufficiency and later septic shock developed. S. aureus and Streptococcus pneumoniae were isolated from blood cultures and tracheal aspirate. In spite of all measures taken, high ventilatory support and targeted antibiotic treatment, severe pulmonary dysfunction with bilateralpneumothorax developed and the patient died of respiratory failure. Later genes encoding PVL were found in the isolated strains of S. aureus. Conclusions Severe progressive necrotising pneumonia with high mortality can be caused by PVL positive S. aureus in imunocompetent patients. To prevent thefuture spread of PVL positive S. aureus infection, the measures as known for methicillin-resistant S. aures, should probable be taken.
Keywords: Adult; bakterijske infekcije; Community-Acquired Infections; Fatal Outcome; Genetics; Infekcije, domačega okolja; Isolation And Purification; Leukocidins; Levkocidini; Odrasli; pljučnica; Pljučnica bakterijska; Pneumonia, Bacterial; Smrtni izid; Staphylococcus Aureus